Differences between willful insolvency and bankruptcy statutory bankruptcy and criminal willful incapacity Liability limits of commercial entities - Akbarkhon Azamov, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This article examines the distinctions between willful insolvency and bankruptcy, focusing on the legal frameworks governing statutory bankruptcy and criminal willful incapacity. It also explores the liability limits of commercial entities within these contexts. While bankruptcy is a legal process that relieves entities unable to meet their financial obligations, willful insolvency involves deliberate actions by individuals or organisations to evade debts, often constituting fraudulent behaviour. Understanding these differences is crucial for legal practitioners and business professionals to navigate the complexities of financial distress and to ensure compliance with applicable laws. The article further delves into the extent of liability that commercial entities and their management may face when engaging in or being accused of willful insolvency, highlighting the importance of adhering to fiduciary duties and the potential legal consequences of their breach.